Genome-wide analysis reveals the emergence of multidrug resistant Stenotrophomonas acidaminiphila strain SINDOREI isolated from a patient with sepsis - Zhang, Ying; Li, Danhua; Yan, Qun; Xu, Ping; Chen, Wei; Xin, Hongya; Wu, Dengshu; Zhou, Mingxiang; Xu, Yajing; Zhang, Ao; Wei, Wenjia; Jiang, Zhiping (Frontiers in Microbiology, 2022)
Stenotrophomonas acidaminiphila, the most recent reported species in genus Stenotrophomonas, is a relatively rare bacteria and is an aerobic, glucose non-fermentative, Gram-negative bacterium. However, little information of S. acidaminiphila is known to cause human infections. In this research, we firstly reported a multidrug-resistant strain S. acidaminiphila SINDOREI isolated from the blood of a patient with sepsis, who was dead of infection eventually. The whole genome of strain SINDOREI was sequenced, and genome comparisons were performed among six closely related S. acidaminiphila strains. The core genes (2,506 genes) and strain-specific genes were identified respectively to know about the strain-level diversity in six S. acidaminiphila stains. The presence of a unique gene (narG) and essential genes involved in biofilm formation in strain SINDOREI are important for the pathogenesis of infections. Strain SINDOREI was resistant to trimethoprim/sulfamethoxazole, ciprofloxacin, ofloxacin, cefepime, ceftazidime, and aztreonam. Several common and specific antibiotic resistance genes were identified in strain SINDOREI. The presence of two sul genes and exclusive determinants GES-1, aadA3, qacL and cmlA5 is responsible for the resistance to multidrug. The virulence factors and resistance determinants can show the relationship between the phenotype and genotype and afford potential therapeutic strategies for infections.